"The Love Laws": Section 377 and the Politics of Queerness in Arundhati Roy's The God of Small Things. Issue 2 (4th May 2017) - Neti, Leila
Abstract: This article examines Arundhati Roy's novel The God of Small Things (1997) in relation to Section 377 of the Indian Penal Code. In it, I show how the literary text aligns with law derived from the colonial era by effectively conflating homosexuality with child sexual abuse, thus restaging the structuring logic and legal history of Section 377. As a result, I argue that Roy's novel, while overtly antagonistic to the disciplinary norms of sexual policing, nevertheless reproduces many of the same proscriptions that it ostensibly aims to critique. Drawing on a range of approaches from psychoanalysis and legal studies to queer theory, the article seeks to frame the novel's representation of the "Love Laws" in the context of the material enforcement of Section 377.